Student and Tutor Satisfaction with Problem-Based Learning in Azerbaijan - Ulkar Sattarova; Wim Groot; Jelena Arsenijevic (MDPI AG, 2021)
This article examines tutors' and students' satisfaction with the implementation of problem-based learning (PBL) at the Azerbaijan University of Architecture and Construction. A total of 28 pilot academic staff members and their students participated in PBL during one semester and received a questionnaire about their experiences at the end of the semester. In total, 649 students were involved in the intervention. Descriptive statistics and factor analyses were used to analyze the data. In total, the response rate among students was 61.7%, and 82.1% among tutors. More than 83% of the students thought that the PBL should be kept as part of the module. A total of 91.3% of tutors agreed that PBL is a great tool for student learning. According to the factor analysis, tutors believed that PBL can develop students' ability for group/team work. Tutors also identified some barriers in applying PBL. For example, they mentioned a lack of relevant skills to apply PBL in higher education. Both students and tutors found the PBL to be a suitable learning tool for their curriculum.